Malaysian TESL students` challenges : instructional use of video production. - Khojasteh, Laleh; Mukundan, Jayakaran; Shokrpour, Nasrin (Sciencedomain International, 2013)

(untitled)
The study aims at identifying the challenges with which Malaysian students of Teaching English as a Second Language (TESL) are faced before, during and after stages of video production process. Study Design: Interpretive. Methodology: In this study an interpretive analysis was done on daily journals and observations of 42 Malaysian TESL students producing a video of a scene of a Shakespearean play, Macbeth. Peer assessment was then applied in order to give students a chance to evaluate their peers’ work. Results: The findings revealed that students encountered various difficulties before, during and after production stages which should be taken into account in teacher training programs. Conclusion: The findings are useful for teachers and teacher education institutions involved in teaching the use of digital video to enhance pedagogy. This study suggests that TESL students should perhaps be exposed to basic video production techniques from early stages of their teacher training in order to be prepared to integrate video production in their future classes to enhance student learning.